Sodium ion battery cathode material and preparation method and application thereof

By using a combination method of surfactant and sodium hydroxide in the preparation of sodium ion battery cathode materials, high dispersion of metal hydroxide precipitation is achieved, the problem of low atomic utilization is solved, the electrochemical performance is improved and the Cost, suitable for industrial production.

CN119191384APending Publication Date: 2024-12-27安徽吉厚智能科技有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411335057.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing methods of preparing cathode materials for sodium ion batteries are difficult to achieve highly uniform dispersion of elements, resulting in a low atomic utilization rate.

Method used

A preparation method is adopted, which involves dissolving the soluble metal salt in deionized water and adding surfactant and sodium hydroxide, stirring and reacting in a reactor, then centrifugation and drying, finally mixing with the sodium salt and heating under nitrogen oxygen atmosphere Sintering, crystal growth is controlled to achieve highly dispersed metal hydroxide precipitation.

Benefits of technology

The sodium ion battery cathode material prepared by this method has good electrochemical properties and high atomic utilization, which is simple and low in cost, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191384A_ABST
    Figure CN119191384A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium-ion battery cathode material and a preparation method and application thereof, and belongs to the technical field of new energy, the preparation method comprises the following steps: respectively dissolving soluble metal salts in deionized water, fully stirring to completely dissolve solids, adding a surfactant, uniformly stirring to obtain a mixed solution, controlling the flow at room temperature, and stirring uniformly to obtain the sodium-ion battery cathode material. Introducing the precipitation solution and the mixed solution into a reactor, stirring and reacting for 1 hour to obtain metal slurry, jointly adding the obtained metal slurry into the reactor, stirring and mixing, centrifuging, washing the precipitate, and drying to obtain a metal hydroxide precipitate; according to the preparation method, control over crystal growth is achieved by controlling the local concentration, the high-dispersion metal cathode material is prepared in cooperation with use of a surfactant, the performance of a battery is improved while the atom utilization rate is increased, and meanwhile the preparation method is simple in process, low in cost and suitable for industrial production. The industrial production is favorably realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy technology, and specifically relates to a sodium ion battery cathode material and a preparation method and application thereof. Background Art

[0002] The large-scale exploitation and use of fossil fuels has not only caused energy depletion, but also seriously polluted the environment. Therefore, green and sustainable energy has been vigorously developed. In order to effectively store and use these new energy sources, large-scale energy storage systems must be developed. In terms of green energy storage, lithium-ion batteries are widely used, but the shortage of lithium resources and high costs have put their sustainable development to the test. Therefore, it is urgent to develop new secondary energy storage batteries with abundant resources and low costs. Compared with lithium-ion batteries, sodium-ion batteries have the characteristics of abundant sodium metal resources, high energy density, sodium does not react with aluminum to form alloys, and low cost. They have become a powerful alternative to lithium-ion batteries.

[0003] In recent years, sodium-ion battery cathode materials have been widely studied, such as layered oxides, polyanionic compounds, Prussian blue and its analogs. Among them, layered oxides (NaTMO2) have attracted widespread attention due to their high electrochemical activity, high theoretical specific capacity and easy synthesis. However, there are many different methods for synthesizing layered oxides (NaTMO2), but it is difficult to achieve highly uniform dispersion of elements, resulting in low atomic utilization. Summary of the invention

[0004] One of the purposes of the present invention is to provide a method for preparing a cathode material for a sodium ion battery, so as to solve the problem that it is difficult to achieve highly uniform dispersion of elements and low atomic utilization rate in conventional preparation methods.

[0005] A second object of the present invention is to provide a sodium ion battery cathode material, which has uniform internal structure distribution and good electrochemical properties.

[0006] A third object of the present invention is to provide an application of the above-mentioned sodium ion battery cathode material in a sodium ion battery.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A method for preparing a sodium ion battery cathode material comprises the following steps:

[0009] Step A, dissolving soluble metal salts in deionized water respectively, stirring thoroughly to completely dissolve the solid to obtain a metal salt solution, adding a surfactant to the metal salt solution, stirring evenly to obtain a mixed solution, adding sodium hydroxide to deionized water, stirring evenly to obtain a precipitate, controlling the flow rate at room temperature, introducing the precipitate and the mixed solution into a reactor, stirring and reacting for 1 hour to obtain a metal slurry, adding the obtained metal slurry into the reactor together, stirring and mixing for 0.5-1 hour, centrifuging, washing the precipitate with deionized water for 3-5 times, and vacuum drying at 60-80° C. to constant weight to obtain a metal hydroxide precipitate;

[0010] Step B: Grind the metal hydroxide precipitate obtained in step A and pass it through a 200-mesh sieve, mix it evenly with the sodium salt, place it in a tubular furnace, heat it to 900-980° C. at a heating rate of 5° C. / min in a nitrogen and oxygen atmosphere, keep it warm for 4-6 hours, and cool it to room temperature with the furnace to obtain a sodium ion battery cathode material.

[0011] Furthermore, the soluble metal salt in step A includes nickel nitrate and manganese nitrate.

[0012] Furthermore, the soluble metal salt in step A also includes ferric nitrate.

[0013] Furthermore, in step A, the volume ratio of the mixed solution to the precipitate is 1:1, the dosage ratio of the soluble metal salt, deionized water, and surfactant in the mixed solution is 0.01-1 mol:1L:0.01g, and the dosage ratio of sodium hydroxide and deionized water in the precipitate is 0.02-3 mol:1L.

[0014] Furthermore, in step A, the flow rate is 0.01-100 L / min.

[0015] Furthermore, the nickel nitrate is nickel nitrate hexahydrate, the iron nitrate is iron nitrate nonahydrate, and the manganese nitrate is manganese nitrate tetrahydrate.

[0016] Furthermore, the surfactant is composed of hexadecyltrimethylammonium bromide and polyethylene glycol 400 in a mass ratio of 1-3:1.

[0017] Furthermore, in step B, the sodium atom in the sodium salt accounts for 0.5-0.9 of the total atomic mole of the metal hydroxide precipitate, and the sodium salt is sodium carbonate.

[0018] Furthermore, in step B, the mass ratio of N2 to O2 in the nitrogen-oxygen atmosphere is 95:5.

[0019] A sodium ion battery cathode material is prepared by the above preparation method.

[0020] A sodium ion battery comprises the sodium ion battery cathode material.

[0021] Beneficial effects of the present invention:

[0022] (1) The present invention controls the crystal growth by controlling the local concentration and uses a surfactant to prepare a highly dispersed metal cathode material, thereby improving the atomic utilization and the performance of the battery. At the same time, the process is simple and low-cost, which is conducive to industrial production.

[0023] (2) In the present invention, a surfactant is introduced into the preparation of metal hydroxide precipitation, specifically hexadecyltrimethylammonium bromide and polyethylene glycol 400. Hexadecyltrimethylammonium bromide is positively charged after dissociation. OH in the system - Under the action of electrostatic attraction, the Ni, Fe, and Mn ions in the solution are distributed along the long chain of hexadecyltrimethylammonium bromide, forming small-particle metal hydroxide precipitates on the long chain. Since hexadecyltrimethylammonium bromide is a long-chain structure, it is easy to collide. The small-particle metal hydroxide precipitates can form a sheet structure through hydrogen bond polymerization. Polyethylene glycol 400 is a non-ionic surfactant and can be adsorbed on the particle surface by steric hindrance, causing repulsion between the particles, thereby achieving the purpose of uniform particles. Therefore, hexadecyltrimethylammonium bromide and polyethylene glycol 400 play a synergistic role and jointly promote the successful acquisition of high-performance sodium-ion battery cathode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present invention will be further described below in conjunction with the accompanying drawings.

[0025] Figure 1 is a scanning electron microscope image of the sodium ion battery cathode material obtained in Example 3 of the present invention;

[0026] Figure 2 is a scanning electron microscope image of the sodium ion battery cathode material obtained in Comparative Example 1 of the present invention;

[0027] Figure 3 This is the XRD diagram of the sodium ion battery cathode material obtained in Example 3 of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] A method for preparing a sodium ion battery cathode material comprises the following steps:

[0031] Step A, add 2.908g of Ni(NO3)2·6H2O to 1000mL of deionized water, stir at room temperature for 10min, then add 0.01g of surfactant, stir for 5min to obtain a mixed solution; add 0.8g of NaOH to 1000mL of deionized water, stir at room temperature for 10min to obtain a precipitate; at room temperature, introduce the mixed solution and the precipitate into a 5L reactor at a rate of 100mL / min, stir and react for 1h to obtain metal slurry 1;

[0032] Take 2.510g of Mn(NO3)2·4H2O and add it to 1000mL of deionized water, stir at room temperature for 10min, then add 0.01g of surfactant and stir for 5min to obtain a mixed solution, take 0.8g of NaOH and add it to 1000mL of deionized water, stir at room temperature for 10min to obtain a precipitate; at room temperature, introduce the mixed solution and the precipitate into a 5L reactor at a speed of 100mL / min, stir and react for 1h to obtain metal slurry 2;

[0033] The metal slurry 1 and the metal slurry 2 were fully stirred and mixed in a 10L reactor for 0.5h, and centrifuged and washed twice at 2000r / min, each time for 10min, and the lower precipitate was taken out and dried in a 60°C forced air drying oven for 12h to obtain a metal hydroxide precipitate;

[0034] Step B: Grind the metal hydroxide precipitate obtained in step A and pass it through a 200-mesh sieve, mix it evenly with sodium carbonate, wherein the sodium atom in the sodium carbonate accounts for 0.5 of the total atomic molar amount of the metal hydroxide precipitate, place it in a tubular furnace, and in a nitrogen and oxygen atmosphere, wherein the mass ratio of N2 to O2 in the nitrogen and oxygen atmosphere is 95:5, heat it to 900°C at a heating rate of 5°C / min, keep it warm for 5 hours, and cool it to room temperature with the furnace to obtain a sodium ion battery cathode material.

[0035] The surfactant is composed of hexadecyltrimethylammonium bromide and polyethylene glycol 400 in a mass ratio of 1:1.

[0036] Example 2

[0037] A method for preparing a sodium ion battery cathode material comprises the following steps:

[0038] Step A, adding 2.908 g of Ni(NO3)2·6H2O to 1000 mL of deionized water, stirring at room temperature for 20 min, adding 0.01 g of a surfactant, stirring for 8 min, and obtaining a mixed solution; adding 0.8 g of NaOH to 1000 mL of deionized water, stirring at room temperature for 20 min to obtain a precipitate; at room temperature, introducing the mixed solution and the precipitate into a reactor at a rate of 75 mL / min, stirring for 1 h, and obtaining a metal slurry 1;

[0039] Take 5.02g of Mn(NO3)2·4H2O and add it to 1000mL of deionized water, stir at room temperature for 20min, then add 0.01g of surfactant and stir for 8min to obtain a mixed solution, take 1.6g of NaOH and add it to 1000mL of deionized water, stir at room temperature for 20min to obtain a precipitate; at room temperature, introduce the mixed solution and the precipitate into the reactor at a rate of 0.1mL / min, stir and react for 1h to obtain metal slurry 2;

[0040] The metal slurry 1 and the metal slurry 2 were fully stirred and mixed in a 10L reactor for 1 hour, and centrifuged and washed twice at 2000r / min, each time for 10 minutes, and the lower precipitate was taken out and dried in a forced air drying oven at 80°C for 12 hours to obtain a metal hydroxide precipitate;

[0041] Step B: Grind the metal hydroxide precipitate obtained in step A through a 200-mesh sieve, mix it evenly with sodium carbonate, wherein the sodium atom in the sodium carbonate accounts for 0.9 of the total atomic molar mass of the metal hydroxide precipitate, place it in a tubular furnace, and in a nitrogen and oxygen atmosphere, wherein the mass ratio of N2 to O2 in the nitrogen and oxygen atmosphere is 95:5, heat it to 980°C at a heating rate of 5°C / min, keep it warm for 4 hours, and cool it to room temperature along with the furnace to obtain a sodium ion battery cathode material.

[0042] The surfactant is composed of hexadecyltrimethylammonium bromide and polyethylene glycol 400 in a mass ratio of 3:1.

[0043] Example 3

[0044] A method for preparing a sodium ion battery cathode material comprises the following steps:

[0045] Step A, adding 290.8 g of Ni(NO3)2·6H2O to 1000 mL of deionized water, stirring at room temperature for 30 min, then adding 0.01 g of a surfactant, stirring for 10 min, to obtain a mixed solution; adding 80 g of NaOH to 1000 mL of deionized water, stirring at room temperature for 30 min to obtain a precipitate; at room temperature, introducing the mixed solution and the precipitate into a reactor at a rate of 75 mL / min, stirring for 1 h, to obtain a metal slurry 1;

[0046] Take 251.0g of Mn(NO3)2·4H2O and add it to 1000mL of deionized water, stir at room temperature for 30min, then add 0.01g of surfactant and stir for 10min to obtain a mixed solution, take 80g of NaOH and add it to 1000mL of deionized water, stir at room temperature for 30min to obtain a precipitate; at room temperature, introduce the mixed solution and the precipitate into the reactor at a speed of 25mL / min, stir and react for 1h to obtain metal slurry 2;

[0047] Take 404g of Fe(NO3)3·9H2O and add it to 1000mL of deionized water, stir at room temperature for 30min, then add 0.01g of surfactant and stir for 10min to obtain a mixed solution, take 80g of NaOH and add it to 1000mL of deionized water, stir at room temperature for 30min to obtain a precipitate, introduce the mixed solution and the precipitate into a 5L reactor at a speed of 25mL / min at room temperature, stir and react for 1h to obtain metal slurry three;

[0048] The metal slurry 1, the metal slurry 2 and the metal slurry 3 were fully stirred and mixed in a 10L reactor for 1 hour, and centrifuged and washed 3 times at 2000r / min, each time for 10 minutes, and the lower precipitate was taken out and dried in a forced air drying oven at 80°C for 12 hours to obtain a metal hydroxide precipitate;

[0049] Step B: Grind the metal hydroxide precipitate obtained in step A and pass it through a 200-mesh sieve, mix it evenly with sodium carbonate, wherein the sodium atom in the sodium carbonate accounts for 0.8 of the total atomic molar weight of the metal hydroxide precipitate, place it in a tubular furnace, and in a nitrogen and oxygen atmosphere, wherein the mass ratio of N2 to O2 in the nitrogen and oxygen atmosphere is 95:5, heat it to 950°C at a heating rate of 5°C / min, keep it warm for 5h, and cool it to room temperature along with the furnace to obtain a sodium ion battery cathode material.

[0050] The surfactant is composed of hexadecyltrimethylammonium bromide and polyethylene glycol 400 in a mass ratio of 1:1.

[0051] Comparative Example 1

[0052] A method for preparing a sodium ion battery cathode material comprises the following steps:

[0053] 7.469g of NiO, 15.969g of Fe2O3, and 7.094g of MnO were taken respectively, ground with sodium carbonate, and passed through a 200-mesh sieve. The sodium atom in sodium carbonate accounted for 0.9 of the total atomic molar weight of NiO, Fe2O3 and MnO. Under a nitrogen and oxygen atmosphere, the mass ratio of N2 and O2 in the nitrogen and oxygen atmosphere was 95:5. The temperature was raised to 950℃ at a heating rate of 5℃ / min, and oxidative sintering was performed for 5h to obtain the sodium ion battery cathode material.

[0054] Comparative Example 2

[0055] A method for preparing a sodium ion battery cathode material comprises the following steps:

[0056] Compared with Example 1, the difference is that the surfactant is hexadecyltrimethylammonium bromide, and the other raw materials, steps and parameters are the same as Example 1.

[0057] Comparative Example 3

[0058] A method for preparing a sodium ion battery cathode material comprises the following steps:

[0059] Compared with Example 1, the difference is that the surfactant is polyethylene glycol 400, and the other raw materials, steps and parameters are the same as Example 1.

[0060] The sodium ion battery cathode material obtained in Example 3 was tested, and the results were Figure 3 As shown by Figure 3 It can be seen that the sodium ion battery cathode material of the present invention was successfully prepared.

[0061] The sodium ion battery cathode materials obtained in Example 3 and Comparative Example 1 were observed using a scanning electron microscope. The results are as follows: Figure 1 and Figure 2 As shown by Figure 1 and Figure 2 It can be seen that both materials have a lamellar structure, but the particle size distribution of the sodium ion battery cathode material prepared in Example 3 is more uniform.

[0062] The sodium ion battery cathode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were respectively used as active materials, active materials, Ketjen black, and polyvinylidene fluoride (PVDF) binder were weighed at a mass ratio of 8:1:1, mixed evenly, and N-methyl-2-pyrrolidone was added to form a slurry. The slurry was evenly coated on an aluminum foil using a scraper, dried in a vacuum drying oven for 12 hours, and a positive electrode sheet (a disc with a diameter of 12 mm) was prepared. In a glove box filled with argon, the positive electrode sheet, the metal sodium sheet, the glass fiber diaphragm, the electrolyte (NaClO4 / PC), and the nickel foam were assembled into button cells in sequence, and the assembled button cells were tested after standing for 12 hours. The electrochemical properties were tested at a constant temperature of 25°C using a Xinwei CT-ZWJ-4S-T-1U test system. The test results are shown in Table 1:

[0063] Table 1

[0064]

[0065] It can be seen from the data recorded in Table 1 that, compared with Comparative Examples 1-3, the sodium ion battery cathode materials obtained in Examples 1-3 have better electrochemical properties.

[0066] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0067] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a sodium ion battery cathode material, characterized in that: The steps include: Step A, dissolving soluble metal salts in deionized water respectively, stirring thoroughly to completely dissolve the solid, adding a surfactant, stirring evenly to obtain a mixed solution, adding sodium hydroxide to deionized water, stirring evenly to obtain a precipitate, controlling the flow rate at room temperature, introducing the precipitate and the mixed solution into a reactor, stirring and reacting for 1 hour to obtain a metal slurry, adding the obtained metal slurry into the reactor together, stirring and mixing for 0.5-1 hour, centrifuging, washing the precipitate, and drying to obtain a metal hydroxide precipitate; Step B: Grind the metal hydroxide precipitate and mix it evenly with the sodium salt, place it in a tube furnace, keep it at 900-980° C. for 4-6 hours in a nitrogen and oxygen atmosphere, and cool it to obtain a sodium ion battery cathode material.

2. The method for preparing a sodium ion battery cathode material according to claim 1, characterized in that: The soluble metal salt in step A includes nickel nitrate and manganese nitrate.

3. The method for preparing a sodium ion battery cathode material according to claim 1, characterized in that: The soluble metal salt in step A also includes ferric nitrate.

4. The method for preparing a sodium ion battery cathode material according to claim 1, characterized in that: The volume ratio of the mixed solution to the precipitate in step A is 1:1, the dosage ratio of the soluble metal salt, deionized water and surfactant in the mixed solution is 0.01-1 mol:1 L:0.01 g, and the dosage ratio of sodium hydroxide and deionized water in the precipitate is 0.02-3 mol:1 L.

5. The method for preparing a sodium ion battery cathode material according to claim 1, characterized in that: The flow rate in step A is 0.01-100 L / min.

6. The method for preparing a sodium ion battery cathode material according to claim 1, characterized in that: The surfactant is composed of hexadecyltrimethylammonium bromide and polyethylene glycol 400 in a mass ratio of 1-3:

1.

7. The method for preparing a sodium ion battery cathode material according to claim 1, characterized in that: In step B, the sodium atom in the sodium salt accounts for 0.5-0.9 of the total atomic mole of the metal hydroxide precipitate, and the sodium salt is sodium carbonate.

8. The method for preparing a sodium ion battery cathode material according to claim 1, characterized in that: The mass ratio of N2 to O2 in the nitrogen-oxygen atmosphere in step B is 95:

5.

9. A sodium ion battery cathode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

10. A sodium ion battery, characterized in that: Including the sodium ion battery cathode material according to claim 9.

Citation Information

Patent Citations

  • Manganese-doped cobaltosic oxide as well as preparation method and application thereof

    CN115215381A

  • Layered oxide precursor, high-entropy layered positive electrode material as well as preparation method and application of layered oxide precursor and high-entropy layered positive electrode material

    CN118084085A

  • Preparation method of layered metal oxide cathode material of sodium-ion battery, cathode plate and sodium-ion battery

    CN118198305A

  • Positive electrode active material for nonaqueous secondary batteries, method for producing same, and nonaqueous electrolyte secondary battery using positive electrode active material

    US20170050864A1

  • Method of producing oxide particles

    US20180186638A1